Pengaruh Teknik Rebozo Terhadap Tingkat Nyeri Kala I Pada Ibu Bersalin Primipara - awwalul wiladatil qodliyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Labor is a natural condition that occurs in women and, in the process,can cause severe pain, and some women can also experience excruciating pain.Pain that maternity mothers cannot overcome can affect the mother's condition inthe form of fatigue, frustration, hopelessness, and cause stress. Stress can cause theweakening of uterine contractions and result in prolonged labor. The Rebozotechnique is a distraction technique that poses less risk or harmful side effects thanpharmacological therapy. This study aimed to determine the effect of the rebozotechnique on the length of the first stage and the pain level during labor at PracticeMidwife Siti Nurul Aini.Methods: This study uses a pre-experimental research design. This study consistedof 2 groups: the treatment and control groups. The research was conducted fromNovember 2019 to June 2020 at Practice Midwife Siti Nurul Aini. The populationin this study were primigravida maternity mothers. The sample of this research wasselected by using the purposive sampling technique. In this study, there were 16respondents in the intervention group and 16 in the control group. The rebozotechnique is given as long as there are contractions during the first stage of labor.The Verbal Descriptor Scale (VDS) measures the pain level. This study used anindependent T-Test data analysis technique.Results: Based on the independent T-test, the P-value was 0.002, and less than0.05, Ha was accepted, so it was concluded that the rebozo technique’s effect onthe length of the first stage of labor. Statistical tests using the Independent T-testobtained a P-value of 0.000, less than 0.05, then Ha was accepted, concluding thatthe rebozo technique had affected the pain level in labor.Conclusion: primigravida maternity who used the rebozo technique progressedfaster than the control group. Meanwhile, the pain level of primigravida motherswho used the rebozo technique was lower than the control group. Therefore, therebozo technique statistically affects the length of labor and the pain level in thefirst stage of labor in primiparous mothers. The results of this study can be used asan alternative non-pharmacological method in midwifery services to overcomelabor pain.